Comorbidities as Risk Factors for Acute and Recurrent Erysipelas - Vesna Brishkoska-Boshkovski; Irena Kondova-Topuzovska; Katerina Damevska; Andrej Petrov (ID-Design/Scientific foundation SPIROSKI, 2019)
Erysipelas is a common infectious skin disease. A typical feature of erysipelas, especially on the lower limbs, is the tendency to reoccur and the study aimed to define the comorbidities associated with it.